Dysregulation of miR-138-5p/RPS6KA1-AP2M1 Is Associated With Poor Prognosis in AML - Yu, Dong-Hu; Chen, Chen; Liu, Xiao-Ping; Yao, Jie; Li, Sheng; Ruan, Xiao-Lan (Frontiers in Cell and Developmental Biology, 2021)
Acute myeloid leukemia (AML) is a malignant disease of hematopoietic stem/progenitor cells, and most AML patients are in a severe state. Internal tandem duplication mutations in FLT3 gene (FLT3-ITD) detected in AML stem cells account for 20 to 30 percent of AML patients. In this study, we attempted to study the impact of the interaction FLT3-ITD mutation and CXCL12/CXCR4 axis in AML, and the possible mechanisms caused by the impact by bioinformatics. Gene set variation analysis (GSVA) revealed that the PI3K-Akt-mTOR pathway with positively correlated to the status of FLT3-ITD mutation. Multiple survival analyses were performed on TCGA-AML to screen the prognostic-related genes, and RPS6KA1 and AP2M1 are powerful prognostic candidates for overall survival in AML. WGCNA, KEGG/GO analysis, and the functional roles of RPS6KA1 and AP2M1 in AML were clarified by correlation analysis. We found that the expression levels of RPS6KA1 and AP2M1 were significantly associated with chemoresistance of AML, and CXCL12/CXCR4 axis would regulate RPS6KA1/AP2M1 expression. Besides, miR-138-5p, regulated by CXCL12/CXCR4 axis, was the common miRNA target of RPS6KA1 and AP2M1. Taken together, the interaction of FLT3-ITD mutation and CXCL12/CXCR4 axis activated PI3K-Akt-mTOR pathway, and the increased expression of RPS6KA1 and AP2M1 causing by hsa-miR-138-5p downregulation, regulates the multi-resistance genes expression leading to drug indications.